2018
DOI: 10.1177/0305735618798027
|View full text |Cite
|
Sign up to set email alerts
|

What makes music relaxing? An investigation into musical elements

Abstract: Research on specific qualities of music used for relaxation has shown conflicting results. The use of different familiar or pre-composed pieces, with many simultaneous changes, might limit the ability to discriminate which musical element is responsible for the relaxation response. To address the latter, we examined the relaxing effects of music on three psychophysiological measures (heart rate, respiration rate, and skin conductance) with one original piece of music, and three modified versions (altering one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
4
11
2
1
Order By: Relevance
“…Consistent with previous research (Barret & Janata, 2016;Hernandez-Ruiz et al, 2018), we found that the characteristics of the participants-such as level of absorption in musicaffected their response to the music experience (Research Question 2). The MAAS scores among conditions were not significantly different when Absorption in Music was included as a covariate.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous research (Barret & Janata, 2016;Hernandez-Ruiz et al, 2018), we found that the characteristics of the participants-such as level of absorption in musicaffected their response to the music experience (Research Question 2). The MAAS scores among conditions were not significantly different when Absorption in Music was included as a covariate.…”
Section: Discussionsupporting
confidence: 90%
“…Researchers and therapists using music may want to consider including a tool such as the AIMS-or a modified shorter version-in pre-screenings or assessments to determine differences in participants' level of immersion in an emotional experience while listening to music. Participants' levels of absorption in music may explain differences in music intervention research studies and clinical practice, and variability in psychological and physiological responses to music when presented with the same or similar stimuli (Hernandez-Ruiz et al, 2018;Sandstrom & Russo, 2013). In addition, future research could determine potential differences between non-musicians versus musicians in their absorption levels and thus their responses to music interventions.…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Once included, the difference among conditions disappeared, supporting a mediating effect of absorption in music. It seems reasonable that the ability and willingness to be "drawn in deeply [by a musical stimulus]" explains, at least partially, the effect of the auditory stimuli on the mindfulness intervention, both for musicians and nonmusicians, consistent with previous literature (Barret & Janata, 2016;Dvorak & Hernandez-Ruiz, 2019;Hernandez-Ruiz et al, 2018;Sandstrom & Russo, 2013). Moreover, a comparison of average absorption in music indicated that musicians have higher scores, which might help explain the lack of significant differences for the auditory stimuli for musicians.…”
Section: Discussionsupporting
confidence: 80%
“…With the understanding that pre-conditioned responses to music seem to mediate the effects of musical stimuli (Barret & Janata, 2016;Hernandez-Ruiz, James, Noll, & Chrysikou, 2018;Sandstrom & Russo, 2013), researchers assessed and controlled for participants' absorption in music. Absorption in music, as defined by the Absorption in Music Scale (AIMS), is a composite variable that measures participants' understanding of emotion in music, their willingness to be drawn into sensory stimuli, and their propensity to be influenced by music (Sandstrom & Russo, 2013).…”
Section: Previous Findings In Mindfulness and Musicmentioning
confidence: 99%